Pulmonary Arteriovenous Malformation presenting as hemothorax in pregnancy: A case report - Chataut, Dinesh; Suwal, Sundar; Subedi, Kamal; Thapa, Ajit; Ghimire, Ram Kumar; Bhatta, Yadav Kumar Deo (Journal of Society of Surgeons of Nepal, 2020)
Introduction: Pulmonary arteriovenous malformation (PAVM) is a rare anomaly, mostly congenital, that tends to increase in size with the influence of various factors. Case report: A primigravida at 37 weeks of gestation presented with acute onset of dyspnea due to right sided hemothorax. Computed tomography showed abnormal vessels with pseudoaneurysm in the right lower lobe and shunting between subsegmental branch of right descending pulmonary artery and right inferior pulmonary vein. Embolization of the lesion was planned after immediate cesarean section. Coil embolization with complete occlusion of supplying artery of the lesion was done. Conclusion: PAVM, although rare can result in fatal complications if untreated. Less invasive image guided coil embolization is a promising treatment modality.